DECENTRALIZATION IN THE EGYPTIAN COASTAL MANAGEMENT - Hossam Samir Ibrahim; Ibrahim Hegazy (JOURNAL OF COASTAL DEVELOPMENT, 2013)
Human impacts, coupled with global climate change are placing increased pressures on coastal environments. During the last three decades, in response to the growing problems of coastal zones, many countries have introduced Integrated Coastal Zone Management (ICZM) as a mechanism to effectively manage the coastal zone and the conflicts of interest arise from competition for coastal space and resources. However many ICZM schemes in the developing countries have failed at the implementation stage as a result of inadequate institutional and management capacity, as well as a lack of decentralization for the community in implementing local integrated coastal management. Hence, decentralization of ICZM is necessary to deal with the extensive geographical problems and the tremendous social and cultural diversity of communities. Egypt provides an excellent case study of this experience. Since the mid-1990s several attempts have been made towards decentralization in Egypt, the process is still in its initial stages and needs support to enhance ICZM implementation. This paper reviews ICZM process in Egypt focussing on discussing decentralization in planning and implementation of ICZM based on interviews with key ICZM actors as well as documentary analysis. It seeks through a critical evaluation to provide some practical recommendations that could help to enhance the implementation of ICZM in Egypt.